FENOMENA KOMUNIKASI PASANGAN PERNIKAHAN ANTARBUDAYA SUKU MELAYU-SUKU MINANG DI KOTA PEKANBARU - Arimbi, Dwinsa; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The intercultural marriages of the Malays and Minang tribes in the city of Pekanbaru which are the most common problems in intercultural marriages are personal or individual backgrounds, different ethnic marriage partners with uncomfortable situations often arise, if someone is very dependent on stereotypes rather than dependent in perception which is directly in nature and becomes a problem in choosing prospective child pairs with different tribes. This study aims to determine the motives, meanings and communication experiences that occur in intercultural marriages of the Minang tribes in Pekanbaru City.This study uses qualitative research methods with a phenomenological approach. The research subjects were 3 husband and wife couples who were selected using the snowball technique. Data collection is done through in-depth interviews, observation, and documentation. To perform data validity, the author uses the technique of extending participation and triangulation. The results of this study indicate that the motive in choosing intercultural marriages of the Malay tribes of Minang in Pekanbaru, namely the motive of the past (because of the motive) is the religion and character of the couple, while the motive comes (in order to motive) that is constant and intact, lasting and happy . The meaning given by partner actors to intercultural marriage is that there is a positive meaning that intercultural marriage teaches mutual respect and mutual understanding on a difference, while the negative meaning of intercultural marriage gives negative perceptual impacts on different tribes so that it involves children in choosing future child partners. And the communication experiences that occur in intercultural marriages of the Minang-Malay ethnic tribe in Pekanbaru City have fun communication experiences that occur in the form of mutual understanding, openness to children in choosing child candidates who are different ethnic groups, love each other, defend each other and each other appreciate. Associated with unpleasant communication experiences, namely negative prejudice towards ethnicity and behavior, and the existence of conflicts between husbands and wives in choosing candidates for different ethnic group.